Case Report: Rare Presentation of Dentin Abnormalities in Loeys-Dietz Syndrome Type I - Jani, Priyam; Duverger, Olivier; Mishra, Rashmi; Frischmeyer-Guerrerio, Pamela A.; Lee, Janice S. (Frontiers in Dental Medicine, 2021)
Loeys-Dietz syndrome type 1 (LDS1) is caused by a mutation in the transforming growth factor-beta receptor 1 (TGFBR1) gene. We previously characterized the oral and dental anomalies in a cohort of individuals diagnosed with LDS and showed that LDS1 had a high frequency of oral manifestations, and most affected individuals had enamel defects. However, dentin anomalies were not apparent in most patients in the cohort. In this cohort, we had identified dentin anomalies in a patient with LDS1, harboring mutation TGFBR1 c.1459C>T (p.Arg487Trp), and in this report, we present clinical and radiographic findings to confirm the dentin anomaly. The proband had gray-brown discoloration of most teeth typical for dentinogenesis imperfecta (DI). A radiographic exam revealed obliterated or very narrow pulp canals, with maxillary anterior teeth being affected more than the posterior teeth. The son of the proband, who also has the same mutation variant, had a history of DI affecting the primary teeth; however, his permanent teeth were normal in appearance at the time of exam. TGFBR1 is expressed by odontoblasts throughout tooth development and deletion of TGFBR1 in mouse models is known to affect dentin development. In this report, we present a rare case of abnormal dentin in two individuals with LDS1. These dental anomalies may be the first obvious manifestation of a life-threatening systemic disease and demonstrate the variable and multi-organ phenotypic effects in rare diseases.